PKM Kelompok Pengusaha Jasa Layanan Bengkel Mobil di Kelurahan Kakaskasen Kota Tomohon Provinsi Sulawesi Utara: PKM Group of Car Repair Service Entrepreneurs in Kakaskasen Village, Tomohon City, North Sulawesi Province - Johan S.C. Neyland; Michael E. Rembet; Irvan R. Rondonuwu (Sam Ratulangi University, 2023)
Partners of the Community Partnership Program (PKM) are service entrepreneurs engaged in workshops that provide car repairs in Kakaskasen Subdistrict, Tomohon City and the types of businesses targeted are small businesses and individuals who have employees or staff of less than five people, with limited financial capabilities resulting in difficulties in investing in tools, training for employees and also generally not being familiar with the tools proposed for training by the proposing team. In business activities as a service provider as well as manufacturing and repairing products, partners experience problems, especially providing precision spare parts products, and the long time taken to complete the work as well as limited management, accounting and administrative capabilities. The Unsrat PKM team will provide training to apply the right technology for these partners, one way is to introduce partners to the tools or machines that have been developed, namely 3D Printers. The automatic production capabilities of this tool can be a solution to partner problems. This tool has a practical design that can be changed in terms of dimensions and function according to the specific needs of partners and the production cost per unit of this tool is also relatively affordable. The PKM team has provided training and assistance to partners in operating this tool. It is hoped that with this program, partners who are productive communities can further improve the quality of services provided and also the quality and variety of products offered. ABSTRAK Mitra Progran Kemitraan Masyarakat (PKM) ini adalah pengusaha jasa layanan yang bergerak dibidang perbengkelan yang melayani perbaikan mobil yg ada di Kelurahan Kakaskasen Kota Tomohon dan jenis usaha yang menjadi target adalah usaha kecil dan perorangan yang mempunyai karyawan atau staf kurang dari lima orang, dengan kemampuan finansial yang terbatas sehingga kesulitan dalam investasi alat, pelatihan bagi kryawan dan juga pada umumnya tidak mengenal alat yang di ajukan untuk pelatihan oleh tim pengusul. Dalam kegiatan usaha selaku penyedia jasa maupun pembuatan dan perbaikan produk, mitra mengalami kendala khususnya menyediakan produk suku cadang yang presisi, dan lamanya waktu yang ditempuh untuk menyelesaikan pekerjaan serta kemampuan manajemen, akuntansi dan administrasi yang terbatas. Tim PKM Unsrat akan memberikan pelatihan untuk menerapan teknologi yang tepat bagi mitra tersebut, salah satu cara adalah memperkenalkan kepada mitra alat atau mesin yang telah dikembangkan yaitu 3D Printer. Kemampuan produksi secara otomatis dari alat ini bisa menjadi salah satu solusi bagi permasalahan mitra. Alat ini memiliki rancangan yang praktis yang secara dimensi dan secara fungsi dapat dirubah sesuai dengan kebutuhan spesifik dari mitra juga biaya produksi per satu unit alat ini juga relatif terjangkau. Pihak tim PKM telah melakukan pelatihan dan pendampingan terhadap mitra dalam mengoperasikan alat tersebut. Diharapkan dengan program ini, mitra yang merupakan masyarakat produktif dapat lebih meningkatkan mutu pelayanan jasa yang diberikan dan juga kualitas serta ragam produk yang ditawarkan.